How Skilled are Hedge Funds? Evidence from their Daily Trades - JAME, Russell (Institutional Knowledge at Singapore Management University, 2012)
We examine the trading skill of hedge funds using transaction-level data. After accounting for trading commissions, we find no evidence that the trades of the average hedge fund outperform across holding periods ranging from one month to one year. However, bootstrap simulations indicate that the trading skill of the top 10% of hedge funds cannot be explained by luck. Similarly, we find that the performance of top hedge funds persists and much of this persistence stems from intra-quarter trading skill. Skilled hedge funds tend to be short-term contrarians and their profits are largely concentrated in smaller, more illiquid stocks. Our findings suggest that while the average hedge fund is unskilled, there are a small minority of skilled funds who persistently create value through liquidity provision.